Videoendoscopic sentinel lymph node detection with icg and bilateral inguinofemoral lymphadenectomy in vulvar cancer comba- ozdemir technique - Comba, Cihan; Erdoğan, Şakir Volkan; Erdoğan, Aliye; Bağdatlı, Ayşenur; Şeker Ataş, Büşra; Demir, Ömer; Özdemir, İsa Aykut (Korean Society of Obstetrics and Gynecology, 2021)
The authors present a surgical film for vulvar cancer surgery, which was performed via video endoscopy. An 88-year-old woman with squamous cell carcinoma of the vulva and who underwent radical vulvectomy was treated with sentinel lymph node (SLN) and bilateral inguinofemoral lymphadenectomy, which is preferably performed via video endoscopic surgery with a near-infrared fluorescence video endoscopy system. SLN mapping was performed using indocyanine green (ICG) and near-infrared fluorescence mapping. SLNs were detected in the left superficial inguinal area. The surgeons performed bilateral inguinofemoral lymphadenectomy. No postoperative early or late complications developed, and the patient was discharged 7 days after surgery. Stage 1B vulvar cancer was identified.
Keywords: Sentinel Lymph Node Biopsy; Videoendoscopic Surgery; Vulvar Cancer